A Bright Side to Family Firms: How Socioemotional Wealth Importance Affects Dark Traits–Job Performance Relationships. (December 2019) - McLarty, Benjamin D.; Holt, Daniel T.
Examining socioemotional wealth's influence at the individual level, an interactionist approach was used to test its moderation effect on the dark personality traits–job performance relationship, using supervisor-employee dyads in family firms. Termed the Dark Triad, dark personality traits include narcissism, psychopathy, and Machiavellianism. Results showed that when supervisors in family firms prioritize socioemotional wealth, the expected relationships between the Dark Triad and employee job performance outcomes (task, citizenship, and counterproductive behaviors) is ameliorated. These findings demonstrate that family firms can create an environment that improves the otherwise negative impact that dark personality has on job performance.